Optimal endowments of public investment: an empirical analysis for the spanish regions - Oscar Bajo-Rubio; Carmen Diaz-Roldan; M. Dolores Montavez-Garces (European Regional Science Association (ERSA), 2001)
The aim of this paper is to estimate the optimal endowments of public investment in Spanish regions. Starting from the standard dynamic neoclassical model, augmented with the public capital stock, the optimal condition for the provision of public capital would be that, in the steady state, the marginal productivities of both public and private capital should be equal. In the empirical application we will estimate a growth equation derived from a simple Cobb-Douglas production function, where the coefficients on the rates of investment in private and public capital would be their respective marginal productivities. The econometric estimation of such an equation with data for the Spanish regions would provide us estimates of the marginal productivities of both factors, which would allow us to infer whether public capital stock in the Spanish regions would be insufficient or otherwise excessive.
Keywords: 330